COENZYME Q10 EFFECT ON NMDA RECEPTOR EXPRESSION AND RETINAL GANGLION CELL DENSITY (Experimental Study in Traumatic Optic Neuropathy Model of Wistar Rat) - FRANSISKA BANJARNAHOR; RISKI PRIHATNINGTIAS; TRILAKSANA NUGROHO; HERMAWAN ISTIADI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Traumatic optic neuropathy is a visual disturbance condition after acute injury to optic nerve. This injury results in retinal ganglion cells ischemic leading to excitotoxicity and apoptosis. Coenzyme Q10 (CoQ10) is an antioxidant and cofactor in electron transport within mitochondria that inhibits glutamate excitotoxicity and thereby preventing retinal ganglion cell apoptosis. This research aims to prove the effect of coenzyme Q10 on NMDA receptor expression and retinal ganglion cell density in rat model of traumatic optic neuropathy. Methods : This study use post-test only randomized controlled groups design. Traumatic optic neuropathy wistar rats model was made by optic nerve crushed method, then given oral CoQ10 100mg/kgBW after 1 hour for 14 days in treatment group. Retinal histopathological specimen was made with immunohistochemistry and Haematoxyllin-eosin staining and examined under microscope with 400x magnification. Data was verified and statistically analyzed. Results : The NMDA receptor expression in the treatment group was significantly lower than control (p=0.009). The retinal ganglion cell density in the treatment group was significantly higher than control (p=0.009). There was a significant correlation between NMDA receptor expression and retinal ganglion cell density in the treatment group (p = 0.012) with a strong negative correlation direction (r = - 0.652). Conclusion : Administration of CoQ10 in traumatic optic neuropathy model rats affects NMDA receptor expression and retinal ganglion cell density. NMDA receptor expression was lower with higher retinal ganglion cell density in the treatment group. NMDA receptor expression was inversely proportional to retinal ganglion cell density in the treatment group.